The proficiency levels of college freshmen in the University of the Philippines for College Mathematics, 1961-1962 - Gonsalvez, Corazon
The study is a survey of the proficiency levels of college freshmen enrolled in the University of the Philippines for college mathematics for the first term, first semester of the school year 1961-1962. There were 613 students tested representing 91 public secondary schools and 26- private secondary schools from all over the Philippines. 293 college freshmen tested came from public high shools and 320 from private high schools. There was a total of 383 boys and 230 girls. 180 of these boys were from public secondary schools and 203 from private secondary schools. The 230 girls comprise 114 from public high schools and 110 from private high schools. A proficiency test in mathematics was constructed by the researcher and given to the said students. the three areas covered were: (1) understanding in mathematical concepts, (2) proficiency in fundamental operations, and (3) proficiency in problem solving. The highest score obtained was 94 percent and the lowest score was 10 percent giving a range of 84. The mean score was 46.80 and 48 percent of the college freshmen studied made scores above the mean while 52 percent were below the mean. Of this data 26 percent of the students from public high schools and 22 percent of students from private high schools were found to be above the mean. The 613 cases studied made a median score of 44.94 and a standard deviation of 20.47 which means that they are widely scattered. The population was grouped according to what schools the students came from, public as well as private high schools; to sex, to the different courses the students were enrolled. The results of the proficiency test given were studies carefully and analyzed item per item. The number of students who answered each item correctly was counted and the percentage of correct answers for each item was then taken. The data on the results of the proficiency examination given showed that the majority of college freshmen enrolled in the U.P. for college freshmen mathematics for the school year 1961-1962, coming from both public and private high schools (1) had a poor understanding in mathematical concepts, (2) had low proficiency in the fundamental operations, and (3) had low proficiency in problem solving. Only a few had a satisfactorily fair understanding of mathematical concepts. There are a few mathematical concepts understood fairly well by the cases studied, like the number concept, relationship of quantities, measurement and measures, like volume, Roman numbers, writing and meaning of decimals and the concept of coefficient in algebra. Geometric concepts fairly understood by the group studied are: right angles, complements of angles, equi-angular triangles, circles, and areas of figures. College freshmen studied had a very poor understanding of percent, ratio, proportion, terms used in graphing like coordinates, abscissa, ordinate, radius vector, median of a triangle, similar triangles and their properties, circumference and diameter of circles, geometric figures,like the different kinds of polygons, and the perimeters of these figures. They, therefore, do not have a clear and thorough understanding of the fundamental mathematical concepts that they need in college freshmen mathematics. Students studied had low proficiency levels in the fundamental operations. They were weak in the operations involving fractions and decimals. They were found to have placed wrong position of decimal points of numbers when adding. They had no notion of the importance of the principle of place value. very poor showing in operations involving negative signs were seen. They failed to follow up the proper procedure in performing the series of fundamental operations. The same was true with the use of brackets, parentheses, and braces. English difficulty was common among them. Only a few got the meaning of "to the nearest tenth" and "to the nearest hundredth." Common mistakes were seen in changing decimals to percents. Simplification was very poor when equations were involved with fractions and decimals. They were weak in looking for the roots of equations, both linear and quadratic. The majority did not understand the process involved in factoring. College freshmen studied had low proficiency in problem solving. Many were not able to grasp the problem situation; failed to determine the known from the unknown quantity; had no systematic procedures in their work. Therefore, they were not competent enough to solve problems in mathematics since their proficiency level was low in problem solving. Proficiency level was just 36 percent and only 211 out of 613 were able to answer one half of the items correctly. 78 college freshmen studied which represented 13 percent were highly proficient in mathematics; 182 of them had average proficiency representing 30 percent. 353 of them which represented 58 percent had low proficiency in mathematics. Students from public high schools seemed to show better perfomance than those coming from private high schools. Those taking up engineering had a better understanding of problem solving type than those taking other courses. Girls used in the study were found to have more difficulty in mathematics than the boys. The latter seemed to be more proficient in mathematics than the former in this group studied.